(untitled) (Bangladesh Pharmaceutical Journal, 2025)
Naproxen, a non-selective NSAID, is used as an analgesic and anti-inflammatory drug. Being a BCS class II drug, it suffers bioavailability problem due to its poor aqueous solubility. Also, naproxen has the potential to cause gastric injury by ion trapping method. The aim of the study is to improve the solubility of naproxen and reduce the potential gastric injury caused by direct contact of the drug with gastric mucosa by formulating pH responsive microspheres. The naproxen microspheres were prepared by solvent evaporation method using Eudragit L100-55 as enteric polymer. In vitro evaluations like entrapment efficiency (%EE), dissolution study, surface morphology (SEM) and drug-excipient interaction (FTIR) were done following the formulation. The entrapment efficiency was found to be the highest and lowest for N6 (1500 mg of Eudragit L100-55) and N1 (250 mg of Eudragit L100-55) formulations, respectively. The microspheres didn’t release any drug in acidic media during dissolution and showed an improved solubility in the pH 6.8 buffer media, indicating site specific drug release in small intestine. In morphological evaluation by SEM, N2 (500 mg of Eudragit L100-55) microspheres were found to be spherical and less than 200 μm in size. Additionally, the FTIR study revealed the compatibility of the drug with the excipients of the formulations. Although enteric microspheres of naproxen seemed to be promising to improve bioavailability and reduce gastric irritation from in vitro perspective, further in vivo evaluation is required to confirm the findings. Bangladesh Pharmaceutical Journal 28(2): 184-192, 2025 (July)